Temporal Soil Bacterial Community Responses to Cropping Systems and Crop Identity in Dryland Agroecosystems of the Northern Great Plains - Ouverson, Tindall; Eberly, Jed; Seipel, Tim; Menalled, Fabian D.; Ishaq, Suzanne L. (Frontiers in Sustainable Food Systems, 2021)
Industrialized agriculture results in simplified landscapes where many of the regulatory ecosystem functions driven by soil biological and physicochemical characteristics have been hampered or replaced with intensive, synthetic inputs. To restore long-term agricultural sustainability and soil health, soil should function as both a resource and a complex ecosystem. In this study, we examined how cropping systems impact soil bacterial community diversity and composition, important indicators of soil ecosystem health. Soils from a representative cropping system in the semi-arid Northern Great Plains were collected in June and August of 2017 from the final phase of a five-year crop rotation managed either with chemical inputs and no-tillage, as a USDA-certified organic tillage system, or as a USDA-certified organic sheep grazing system with reduced tillage intensity. DNA was extracted and sequenced for bacteria community analysis via 16S rRNA gene sequencing. Bacterial richness and diversity decreased in all farming systems from June to August and was lowest in the chemical no-tillage system, while evenness increased over the sampling period. Crop species identity did not affect bacterial richness, diversity, or evenness. Conventional no-till, organic tilled, and organic grazed management systems resulted in dissimilar microbial communities. Overall, cropping systems and seasonal changes had a greater effect on microbial community structure and diversity than crop identity. Future research should assess how the rhizobiome responds to the specific phases of a crop rotation, as differences in bulk soil microbial communities by crop identity were not detectable.